2013
DOI: 10.1068/p7377
|View full text |Cite
|
Sign up to set email alerts
|

Change Blindness in a Dynamic Scene Due to Endogenous Override of Exogenous Attentional Cues

Abstract: Word Count = 1264Running Head: Failure to detect dynamic scene changes due to endogenous control. ABSTRACT [148 out of 150]Change blindness is a failure to detect changes if the change occurs during a mask or distraction. Without distraction, it is assumed that the visual transients associated with the change will automatically capture attention (exogenous control) leading to detection. However, visual transients are a defining feature of naturalistic dynamic scenes. Are artificial distractions needed to hide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…For example, the magician might ask a person to count the number of face cards among those being dealt onto the table. Since their attentional resources are occupied by this, they will fail to notice things going on elsewhere (Smith et al, 2013 ). A related form of this—which also plays a central role in Bruno's taxonomy (Section Joe Bruno: Anatomy of misdirection)—is the creation of confusion .…”
Section: A Psychologically-based Taxonomymentioning
confidence: 99%
“…For example, the magician might ask a person to count the number of face cards among those being dealt onto the table. Since their attentional resources are occupied by this, they will fail to notice things going on elsewhere (Smith et al, 2013 ). A related form of this—which also plays a central role in Bruno's taxonomy (Section Joe Bruno: Anatomy of misdirection)—is the creation of confusion .…”
Section: A Psychologically-based Taxonomymentioning
confidence: 99%
“…However, slight differences in eye movements may have occurred across instruction conditions such as more anticipatory saccades to the next card in the simpler Instruction 1 compared to the other instruction conditions. Although earlier studies have suggested that fixation location does not influence change detection during such dynamic scenes ( Triesch et al, 2003 ; Kuhn and Tatler, 2005 ; Kuhn et al, 2008 ; Kuhn and Findlay, 2010 ; Smith et al, 2012 , 2013 ) we cannot rule out the possibility that subtle eye movement differences may have dissociated attention from the critical card as it changed, providing an opportunity for change blindness. Future studies should monitor eye movements during this interactive task to discount this possibility.…”
Section: Discussionmentioning
confidence: 71%
“…For example, change blindness is greater for objects away from areas of central interest in a photograph when changes occur across flickers ( Rensink et al, 1997 ), is created by non-occluding “mudsplashes” that involuntarily attract attention ( O’Regan et al, 1999 ) and increases with distance from fixation when the change occurs across a saccade ( Henderson and Hollingworth, 1999 ). The impact of fixation location on change blindness has also been clearly demonstrated in a specially designed card trick ( Smith et al, 2013 ). In this trick a deck of blue-backed cards was switched for a deck of red-backed cards in full sight (i.e., without occlusion or distraction) but participants failed to notice as their eyes were fixated on a different location as the cards were dealt.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Existing paradigms tend to focus on how to prevent spectators from detecting ostensibly visible elements of the methods behind magic effects. These failures to see have been associated with phenomena such as inattentional blindness ( Kuhn and Tatler, 2005 ; Barnhart and Goldinger, 2014 ) and change blindness (e.g., Johansson et al, 2005 ; Smith et al, 2012 , 2013 ). But misdirection does not only involve inducing failures to see, it can also involve inducing misperceptions of illusory objects.…”
Section: Introductionmentioning
confidence: 99%